Long-term turnover of the sponge fauna in Faro Lake (North-East Sicily, Mediterranean Sea). Issue 4 (1st October 2016) - Marra, M. V.; Bertolino, M.; Pansini, M.; Giacobbe, S.; Manconi, R.; Pronzato, R.
Abstract: The paper focuses on the long-term taxonomic composition and distribution of the shallow-water sponge fauna from the meromictic–anchialine coastal basin Faro Lake (Southern Italy), comparing recent qualitative field data with literature data over a 50-year period. The Faro Lake shallow water currently hosts 24 conspicuous species of Porifera belonging to 21 genera, 18 families, eight orders, three subclasses and two classes, i.e. Demospongiae (23) and Calcarea (one). The comparison between the present and past status of the sponge fauna showed a high turnover, with 15 new colonizers and only nine persistent species. Thirteen species reported in the literature are missing, suggesting the occurrence of remarkable changes in the faunal composition during the last 50 years. The analysis of the geographic distribution of each species allowed us to outline the prevalent North Atlantic affinity of the sponge community. Worthy of note is the new record of the alien calcareous sponge Paraleucilla magna of cryptogenic origin.